Incidence and risk factors of osteoporotic status in outpatients who underwent gastrectomy for gastric cancer. Issue 5 (23rd April 2020) - Namikawa, Tsutomu; Yokota, Keiichiro; Iwabu, Jun; Munekage, Masaya; Uemura, Sunao; Tsujii, Shigehiro; Maeda, Hiromichi; Kitagawa, Hiroyuki; Karashima, Takashi; Kumon, Masamitsu; Inoue, Keiji; Kobayashi, Michiya; et al.
Abstract: Background and Aim: Disorders in bone metabolism have long been recognized as typical sequelae of gastrectomy; however, the pathogenesis has not been fully elucidated, resulting in a variation of reported incidence. This study aimed to evaluate current bone health by measuring bone mineral density (BMD) in patients treated by gastrectomy for gastric cancer, with a focus on incidence and risk factors of osteoporosis. Methods: The study enrolled 81 patients who underwent gastrectomy for gastric cancer at Kochi Medical School. BMD of the lumbar spine was measured by dual‐energy X‐ray mineral absorptiometry, with the results expressed as a percentage of the young adult mean (YAM). Clinical data were also obtained to investigate associations with BMD. Results: Of the 81 study patients, 12 (14.8%) were deemed to have osteoporosis, defined by a percentage of YAM <70, with a dominance of females over males (66.7% vs 17.4%; P < 0.001). The median body weight, hemoglobin concentration, and serum alkaline phosphatase (ALP) level of the patients with osteoporosis was significantly lower than in those with a percentage of YAM ≥70 group (39.6 kg vs 53.1 kg, P < 0.001; 10.9 mg/dL vs 12.5 mg/dL, P = 0.010; 210 U/L vs 251 U/L, P = 0.002). Further analyses revealed a significant positive correlation between body weight and percentage of YAM (r = 0.441, P < 0.001). Despite the administration of bisphosphonates in these patients during this study, one acquired a bone fracture. Conclusion: Osteoporosis was found in 14.8% of postoperative gastric cancer patients, with female gender, low body weight, and low ALP proposed as risk factors for osteoporosis and thus future bone fracture. Abstract : We found osteoporosis in 14.8% of outpatients receiving periodic follow‐up physical examinations after gastrectomy for gastric cancer, and identified low BMD as a clear indicator of increased bone fragility and risk for fracture in these patients. In these patients, female gender, low body weight, low hemoglobin, and low ALP were potential risk factors for osteoporosis.